Isolation and Antimicrobial Susceptibility Patterns of Campylobacter Species among Diarrheic Children at Jimma, Ethiopia - Tafa, Belay (Int J Bacteriol, 2014)
Introduction. Campylobacter is one of the leading bacterial causes of food-borne disease. The prevalence of Campylobacter species resistant to antimicrobial agents is increasing. This study is intended to determine prevalence and antimicrobial susceptibility patterns of Campylobacter species among under-five children with diarrhea. Methodology. A cross-sectional study was conducted among 227 under-five children with diarrhea from July to October 2012 at Jimma town. Isolation and identification of Campylobacter species were performed using standard bacteriological techniques. Antimicrobial susceptibility test was performed following standard protocol. Chi-square and Fisher's exact tests were used for analysis. Results. From 227 under-five children, 16.7% were positive for Campylobacter spp.; isolates, C. jejuni, C. coli, and C. lari, accounted for 71.1%, 21.1%, and 7.9%, respectively. Higher rate of resistance was observed to ampicillin 76.3%, trimethoprim-sulfamethoxazole (68.4%), tetracycline (39.5%), chloramphenicol (31.6%), clindamycin (26.3%), and doxycycline (23.7%). Erythromycin, ciprofloxacin, gentamicin, norfloxacin, and nalidixic acid were effective for more than 80% of the isolates. Multiple drug resistance was observed among 78.9% of all the three spp. Conclusions. Isolation rate of Campylobacter spp. was high. C. lari was reported for the first time at this study area. Higher rate of resistance was observed to the commonly used drugs.